The end-Cretaceous mass extinction event--Recovery and evolution of life - Schaefer, Bettina (Curtin University, 2021)
The end-Cretaceous mass extinction is linked to an asteroid impact 66 Ma ago. Biomarker and stable isotopes are used to summarise the extinction event and the recovery of microbial life in the Chicxulub impact crater. First evidence of photosynthesis is observed 30,000 years after the impact. Additional, environmental 16S rRNA gene profiling revealed that the impact induced changes in the lithology 66 Ma ago are still shaping the microbial community in the deep subsurface today.